Władysław Machejek – partyjny literat - Drabik, Sebastian (Komunizm: System - Ludzie - Dokumentacja, 2023)
During the period of the Polish People’s Republic Władysław Machejek (1920– 1991) was the most controversial person in the literary circle of Kraków. Not only was he a writer, but also an active member of the Polish United Workers’ Party. He had an important role in the party’s structures in the region. This text is a description of Machejek, a controversial figure who provoked extreme emotions, and his influence on the party between 1950s and 1980s. Machejek also influenced the the Union of Polish Writers.